The Effect of Brand Image and Price on Customer Satisfaction in Purchasing Es Kopi Susu Keluarga at Familymart Jakarta - Muhammad Sedky; Setyo Riyanto (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
Coffee has become a lifestyle requirement for people in Jakarta. Many new businesses take advantage of this opportunity; one of them is FamilyMart. FamilyMart is a Japanese retail company that also sells food and beverages, one of the popular products is the iced Kopi Kopi Keluarga. The purpose of this research is to analyze and explain the effect of corporate image, store image, product image and price on customer satisfaction in purchasing Es Kopi Susu Keluarga. This research method uses descriptive methods and quantitative approaches using questionnaires as research instruments. The number of samples used was 59 respondents. Conclusion of the results of the analysis of this study found that the variables significantly influence the variable of customer satisfaction.